WOMAN IMAGES IN THE NOVEL TERUSIR BY BUYA HAMKA (A FEMINIST LITERARY CRITICISM) - Mei Yana Gea; Sri Minda Murni; Syamsul Bahri (LINGUISTICA, 2019)
This study was aimed to analyze the woman images based on the main chracter that is consisted in the novel Terusir and to find how the woman images appeared in the novel Terusir. This research was qualitative descriptive research. The data were taken from the sentences in the novel Terusir. The data collected by documentary technique. This research deals with theory which is conducted by Sugihastuti (2000), where she said woman images is the images of woman roles in social life, divided into physic, psychology and social context. There are beautiful, cosmetic defender nd sexual pleasure in the physic images. There are great sense of belonging, patient, vicious creature, faith defender, generous, obedient and feminist in psychology images. And the last, there are naive creature, construct, angel in the house, devoted to the family, whore is broken, and widow bad in the social images.  And the woman images are described from the main character named Mariah and the other characters.Keywords : Novel, feminist literary criticism, woman images